Consumers’ profiles in purchasing Korean products: Malaysia context / Azurin Sani … [et al.] - Sani, Azurin; Syed Omar, Syed Ashrene; Mohamed Thaheer, Ahmad Shazeet; Mohd Zin, Nur Athirah (2022)
The study analyzes customer profiling in purchasing Korean products in Kuala Lumpur, Malaysia. The focus of this study is to identify the type of Korean products interested by Malaysian consumers. Apart from this research studies the Korean wave factors that influence customer purchase intention toward Korean products. Consequently, this research also studies the type of Korean products that might influence customer purchases. The research objective is to identify the consumers' profiling in terms of age, gender, occupation, and race that influence the purchasing of Korean products. Another objective of this study is to identify the type of Korean products purchased by Malaysians. Questionnaires were distributed online via a social media platform. The respondents focus on random consumers that love to buy Korean products. Descriptive analysis was used to evaluate the data collected.